Productive Performance and Immune Response of Laying Hens as Affected by Dietary Propolis Supplementation - Galal, A.; El-Motaal, A.M. Abd; Ahmed, A.M.H.; Zaki, T.G. (International Journal of Poultry Science, 2008)
An experiment was conducted to evaluate the efficacy of supplemental Propolis on productive performance and immune response of laying hens. One hundred and twenty Hy-Line White strain were divided into four groups of 30 each. They were fed 0, 50, 100 and 150 mg of supplemental Propolis for 8 weeks (46-54wk). Chickens in all groups were reared under the same environmental, managerial and hygienic conditions. Feed and water were supplied ad libitum. The average high and low ambient temperatures recorded during the experimental period were 22.6 and 15.8oC, respectively. The performance data revealed that the laying hens fed diet containing 100 and 150 mg Propolis were significantly consumed more feed than control-group. Similar trend, but not statistically significant, was observed for hens fed diet added 50 mg Propolis. With respect to egg mass, it could be noticed that the laying hens fed diet containing 100 and 150 mg Propolis significantly produced heaviest egg mass compared to control-group. The hens fed diet added 50 mg Propolis were intermediate. The increase feed intake and egg mass in propolis groups, resulting in significantly improve feed conversion ratio compared to control-group. Eggshell quality was significantly affected by Propolis supplementation, whereas the percentage and thickness of eggshell were significantly increased in the eggs produced from hens fed diet containing medium or high level of Propolis. In accordance to hematological parameters, the medium or high level of dietary Propolis significantly increased hematocrit level, plasma total protein and globulin. Conversely, the plasma cholesterol and liver enzymes were significantly reduced when laying hens fed diet containing 100 or 150 mg Propolis. In vivo cell-mediated immune response as measured by PHA-P stimulation (wattle) revealed that the laying hens fed diet added 50, 100 and 150 mg Propolis/kg had significantly hyper responder compared to control-fed group. Concerning white blood cells differentiation, the present results speculated that the 100 and 150 mg Propolis supplementation significantly decreased heterophils count and increased lymphocytes count when compared with the control-group. In conclusion, it can be concluded from the above study that supplementation of Propolis at 100 or 150 mg is beneficial for improving the performance and immunity and for exploiting the full genetic potential of the commercial laying hens.